PEMETAAN KERUKUNAN DAN KERAWANAN SOSIAL KEHIDUPAN UMAT BERAGAMA DI KABUPATEN KUANTAN SINGINGI - Kurnial Ilahi; Jamaluddin Rabain (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2011)
Research works through effort build and nurse aught social harmonies all this time, at a swoop look for more new altenative mengena and gets social reality basis that Current deep society . This study is constituted an assumption, that problem indonesian nation national reconciliation that observable at current surface, was obviously of cause of that very simple as it were dipersepsikan there are many circle, and was obviously too same problem which is faced among one nation with another nation at this. Therefore, seen to need pengkajian in order to map reconciliation condition and society social crisis at areas that its heterogeneous resident included at Kuantan Singingi.